Nigral Neuroinflammation and Dopaminergic Neurons in Parkinson's Disease and Atypical Parkinsonisms - Backman, Emmilotta A.; Gardberg, Maria; Luntamo, Laura; Peurla, Markus; Vahlberg, Tero; Borghammer, Per; Stefanova, Nadia; Wenning, Gregor; Kaasinen, Valtteri (Wiley, 2026)
Objective: To investigate the role of neuroinflammation in the substantia nigra pars compacta (SNc) across different parkinsonian disorders-Parkinson's disease (PD), progressive supranuclear palsy (PSP), and multiple system atrophy (MSA)-by examining SNc dopaminergic neuron counts, neuroinflammatory T cells, and microglial activity.
Methods: Postmortem neuropathological samples were collected from 79 individuals (PD, n = 38; PSP, n = 15; MSA, n = 14; controls, n = 12). The density of SNc tyrosine hydroxylase (TH)-positive neurons, T cells (CD3+, CD4+, and CD8+), and Iba1 expression (Iba1-positive microglia/macrophages) were examined in the SNc and crus cerebri. Demographic and clinical data were gathered from patient histories.
Results: PSP patients had 89 to 212% more nigral CD3+, CD4+, and CD8+ T cells compared to MSA patients (p < 0.04), 125 to 178% more CD3+ and CD4+ T cells than healthy controls (p < 0.002), and 95% more CD4+ T cells than PD patients (p = 0.001). Iba1 expression in the SNc was higher in PD patients than in MSA patients (p = 0.004), with no significant differences observed across other conditions. There was a negative association between disease duration and SNc CD3+ T cell density (p = 0.002), and a positive correlation between nigral dopaminergic neuron density and CD3+ density, CD8+ density, and Iba1 expression in PD patients.
Interpretation: The study reveals distinctive neuroinflammatory patterns in the SNc, with T cell-mediated inflammation prominent in PSP and microglia-mediated inflammation in PD. PSP and MSA show greater SNc dopaminergic neuron loss compared to PD. Increased neuroinflammatory response is seen in earlier disease stages, diminishing with greater neuron loss, which may inform disease progression understanding and therapeutic strategies. ANN NEUROL 2025.